2022
DOI: 10.2147/jir.s372543
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of NAD+ by Dunnione Ameliorates Imiquimod-Induced Psoriasis-Like Dermatitis in Mice

Abstract: Background Dunnione has anti-inflammatory properties arising from its ability to alter the ratio of NAD + /NADH through NAD(P)H quinone oxidoreductase 1 (NQO1) enzymatic action, followed by subsequent inhibition of NF-κB and inflammatory cytokines. Psoriasis is a chronic, inflammatory skin disorder in which the IL-23/Th17 axis plays an important role in inflammation. However, it is unclear whether modulation of NAD + levels affects psoriasis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We have already shown that the topical composition of NAD + can effectively be used for the treatment of psoriasis, with effects comparable to conventional therapy with anthralin [13]. More recent research has confirmed that the augmentation of NAD + can result in the amelioration of psoriasis-like dermatitis [14]. This effect is linked to elevated Sirt1 activity, which is an NAD + -dependent process.…”
Section: Resultsmentioning
confidence: 92%
“…We have already shown that the topical composition of NAD + can effectively be used for the treatment of psoriasis, with effects comparable to conventional therapy with anthralin [13]. More recent research has confirmed that the augmentation of NAD + can result in the amelioration of psoriasis-like dermatitis [14]. This effect is linked to elevated Sirt1 activity, which is an NAD + -dependent process.…”
Section: Resultsmentioning
confidence: 92%